Infection of Primary Bovine Macrophages with Mycobacterium avium Subspecies paratuberculosis Suppresses Host Cell Apoptosis - Kabara, Edward; Coussens, Paul M. (Frontiers in Microbiology, 2012)
Mycobacterium avium subspecies paratuberculosis (MAP) is one of the most important infectious agents in the American dairy industry. MAP is survives intracellularly in macrophages by preventing normal phagosome maturation utilized to destroy bacteria. Macrophages often undergo apoptotic cell death in response to intracellular pathogens. This allows for efficient presentation of bacterial antigens to adaptive immune cells, a process known as efferocytosis. Recent studies with Mycobacterium tuberculosis (MTB), a mycobacterium related to MAP, showed that macrophages infected with MTB are less likely to undergo apoptosis than control, uninfected cells. It is proposed that regulation of macrophage apoptosis is an important immune evasion tactic for MTB. Based on similarity of MAP and MTB, we hypothesized that MAP infected macrophages would be resistant to apoptosis relative to uninfected cells. Our results demonstrate that populations of MAP-infected macrophages contain fewer apoptotic cells than similar populations of control cells, and that MAP-infection reduces sensitivity of infected macrophages to induction of apoptosis by H2O2. MAP-infected cells also contain reduced caspase activity relative to uninfected cells. Reduced caspase activity in infected macrophages is maintained after strong H2O2 stimulation. This reduction in activity is accompanied by a reduction in transcription of caspase genes when compared to control, uninfected cells. MAP-infection also drastically effects expression of several host cell proteins important for regulation of apoptosis. Studies using mutant MAP strains demonstrate the importance of several bacterial factors in control of host macrophage apoptosis. Together these data demonstrate that MAP specific factors may prevent caspase activation and apoptosis related protein expression leading to decreased spontaneous host cell apoptosis and decreased sensitivity to apoptosis inducing agents.